STUDI KASUS: PERFORMA USAHA PENDEDERAN IKAN KERAPU CANTANG (Epinephelus fuscoguttatus x Epinephelus lanceolatus) DI SITUBONDO, JAWA TIMUR - Vinasyiam, Apriana; Hayati, Rizkhni Nuril; Astari, Belinda (Universitas Mataram, 2025)
The nursery phase of hybrid grouper (kerapu cantang; Epinephelus fuscoguttatus x Epinephelus lanceolatus) farming is a crucial business segment, as it serves as a key link in the seed supply chain for grow-out operations. This study aims to analyze the profitability aspects of nursery operations at a commercial farm in Indonesia, using a trading enterprise (UD) in Situbondo, East Java, as a model. The research was conducted by collecting both primary and secondary data through interviews. Observations revealed an average fish survival rate of 86.5%, resulting in an estimated annual production of 99,000 fingerlings using a total of 14 nursery tanks measuring 4x3x1 m³ each. The largest investment cost components were the nursery tanks (40%) and water installation systems (33%). The main fixed and variable cost components were employee salaries (69%) and feed (84%), respectively. Financially, the nursery operation is profitable, generating an annual profit of IDR 274,338,923 and an R/C ratio of 1.59. The investment payback period is estimated at 1.68 years (20 months). Optimization of operations is recommended through production scale-up in the second year, by reducing feed costs, or by increasing the fry production.